Atomic layer deposition of vanadium oxide films for crystalline silicon solar cells. Issue 1 (5th November 2021) - Costals, Eloi Ros; Masmitjà, Gerard; Almache, Estefania; Pusay, Benjamin; Tiwari, Kunal; Saucedo, Edgardo; Raj, C. Justin; Kim, Byung Chul; Puigdollers, Joaquim; Martin, Isidro; Voz, Cristobal; Ortega, Pablo
Abstract : We have fabricated n-type silicon solar cells using ALD deposited vanadium oxide as the front transparent contact. Abstract : Transition metal oxides (TMOs) are promising materials to develop selective contacts on high-efficiency crystalline silicon solar cells. Nevertheless, the standard deposition technique used for TMOs is thermal evaporation, which could add potential scalability problems to industrial photovoltaic fabrication processes. As an alternative, atomic layer deposition (ALD) is a thin film deposition technique already used for dielectric deposition in the semiconductor device industry that has a straightforward up scalable design. This work reports the results of vanadium oxide (V2 O5 ) films deposited by ALD acting as a hole-selective contact for n-type crystalline silicon (c-Si) solar cell frontal transparent contact without the additional PECVD passivating layer. A reasonable specific contact resistance of 100 mΩ cm 2 was measured by the transfer length method. In addition, measurements suggest the presence of an inversion layer at the c-Si/V2 O5 interface with a sheet resistance of 15 kΩ sq −1 . The strong band bending induced at the c-Si surface was confirmed through capacitance–voltage measurements with a built-in voltage value of 683 mV. Besides low contact resistance, vanadium oxide films provide excellent surface passivation with effective lifetime values of up to 800 μs. Finally, proof-of-concept both-side contacted solar cells exhibit efficiencies beyond 18%, shedding light on the possibilities of TMOs deposited by the atomic layer deposition technique.